Ophiocordyceps anocheti sp. nov. a new ant-parasitizing species from China - Xie, Shu-Qiong; Yang, Yu; Xiao, Yuan-Pin; Lu, Yong-Zhong; Nalumpang, Sarunya (Phytotaxa, 2025)
Ophiocordyceps is the largest genus in Ophiocordycipitaceae, known for its diverse host range and ecological adaptability, particularly in tropical and subtropical regions. Southwestern China is a hotspot for its species diversity. Ophiocordyceps fungi typically parasitize insects through specialized adaptations in their life cycle. In this study, a new species, Ophiocordyceps anocheti, a parasite of red ants (Anochetus sp., Ponerinae) is described. It is distinguished from other Ophiocordyceps species in having slender synnemata lacking a swollen head, stout phialides, and hyaline, smooth, one-celled conidia. Phylogenetic analysis based on six loci (SSU, LSU, ITS, tef-1α, rpb1, and rpb2) confirms Ophiocordyceps anocheti as a novel species within the genus.